Amelioration of myocardial ischemia/reperfusion injury in diabetes: A narrative review of the mechanisms and clinical applications of dexmedetomidine - Sun, Meng; Wang, Rong; Xia, Rui; Xia, Zhengyuan; Wu, Zhilin; Wang, Tingting (Frontiers in Pharmacology, 2022)
Mechanisms contributing to the pathogenesis of myocardial ischemia-reperfusion (I/R) injury are complex and multifactorial. Many strategies have been developed to ameliorate myocardial I/R injuries based on these mechanisms. However, the cardioprotective effects of these strategies appear to diminish in diabetic states. Diabetes weakens myocardial responses to therapies by disrupting intracellular signaling pathways which may be responsible for enhancing cellular resistance to damage. Intriguingly, it was found that Dexmedetomidine (DEX), a potent and selective α2-adrenergic agonist, appears to have the property to reverse diabetes-related inhibition of most intervention-mediated myocardial protection and exert a protective effect. Several mechanisms were revealed to be involved in DEX’s protection in diabetic rodent myocardial I/R models, including PI3K/Akt and associated GSK-3β pathway stimulation, endoplasmic reticulum stress (ERS) alleviation, and apoptosis inhibition. In addition, DEX could attenuate diabetic myocardial I/R injury by up-regulating autophagy, reducing ROS production, and inhibiting the inflammatory response through HMGB1 pathways. The regulation of autonomic nervous function also appeared to be involved in the protective mechanisms of DEX. In the present review, the evidence and underlying mechanisms of DEX in ameliorating myocardial I/R injury in diabetes are summarized, and the potential of DEX for the treatment/prevention of myocardial I/R injury in diabetic patients is discussed.